Pengaruh Komposisi Dewan Komisaris terhadap Sinkronisitas Harga Saham - Susanto, Auberta Danice; Robiyanto, Robiyanto (Fakultas Ekonomi Universitas Kadiri, 2020)
This study shows the effect between board of commissioners composition and stock price synchronicity. Board of commissioners composition is proxied on board size, proportion of women, and board independence. The study uses control variables includes company size, PBV, and leverage. Samples from manufacturing sector in Indonesia Stock Exchange during period of 2015 to 2018, using purposive sampling and panel regression analysis. The results show that board of commissioners, proportion of women, and board independence have no effect to reduce stock price synchronicity. Company size need to be controlled to reduce stock price synchronicity. PBV have no effect to reduce stock price synchronicity and leverage can reduce stock price synchronicity.